Ultrastructure of the tropharium of Dactylopius coccus Costa, 1829 (Hemiptera: Coccoidea: Dactylopiidae). - Ramírez-Cruz, Arturo (Instituto de Ecología, A.C., 2012)
An ultrastructural description of adult females tropharium of Dactylopius coccus Costa, 1829, by electron microscopy transmission was realized. The tropharium is surrounded by an inner epithelial sheath and by a tunica propria. Furthermore, it contains large nurse cells with irregular-shaped nuclei and their nuclear membrane is abundantly perforated with nuclear pores; further one or morenucleoli were seen. Moreover their cytoplasm contained large numbers of ribosomes and mitochondria, but scarce rough endoplasmic reticulum. Neither smooth endoplasmic reticulum nor Golgi complex were observed. In the nurse cells of the females of two days-old, bacteria apparently symbionts were found, but their possible role in the ovarian physiology is unknown. Some nurse cells of females at ten days-old, had small groups of annular lamellae, which could be related with a degenerative process in these cells. The trophic cords were made of great number of microtubules and between them numerous ribosomes and mitochondria, many of them of elongated form.